Reconstruction with omental flap and negative pressure wound therapy after total pelvic exenteration of anal fistula cancer: a case report - Akira Komono; Gumpei Yoshimatsu; Ryuji Kajitani; Yoshiko Matsumoto; Naoya Aisu; Suguru Hasegawa (Surgical Case Reports)
Abstract Introduction Surgery for anal fistula cancer (AFC) associated with Crohn’s disease usually entails extensive perineal wounds and dead space in the pelvis, which is often filled with a myocutaneous flap. However, use of a myocutaneous flap is invasive. We report a case of total pelvic exenteration (TPE) for AFC in which a myocutaneous flap was avoided by using an omental flap and negative pressure wound therapy (NPWT). Case presentation The patient was a 47-year-old woman who had been treated for Crohn’s disease involving the small and large intestine for 30 years and had repeatedly developed anal fistulas. She was referred with a diagnosis of AFC that had spread extensively in the pelvis. We performed laparoscopic TPE via a transperineal endoscopic approach. To prevent infection in the large skin defect and extensive pelvic dead space postoperatively, the perineal wound was reconstructed using an omental flap and NPWT. During 20 days of NPWT, the wound steadily decreased in size and closed on postoperative day (POD) 20. She was discharged without complications on POD 30. Discussion NPWT is useful for preventing perineal wound infection and promoting granulation tissue formation. However, direct contact with the intestine may lead to intestinal perforation. In this case, the combination of an omental flap with NPWT effectively prevented surgical site infection. The flap filled the large pelvic dead space and physically separated the intestine from the polyurethane foam used for NPWT. Conclusion NPWT and an omental flap may become an option when performing TPE.